Introduction to electromagnetism from Coulomb to Maxwell - Sibley, M. J. N. (Martin J. N.) (CRC Press, 2021)
"This edition aims to expand the on the first edition and take the reader through to the wave equation on coaxial cable and free-space by using Maxwell's equations. The new chapters will include time varying signals and fundamentals of Maxwell's equation"